Communicating in the 21st century - Eunson, Baden (Milton, Qld. : John Wiley & Sons, Australia, 2006)
" Second edition, a comprehensive and referenced coverage in the field of communication in Australia." -- back cover.
Previous ed.: 2005.
Includes bibliographical references (p. 802-803) and index.
Keywords: Communication -- Social aspects -- Australia; Communication -- Research -- Australia; Business communication -- Australia; Knowledge management -- Australia; Communication in personnel management -- Australia